Kondisi Sosial Ekonomi Siswa Putus Sekolah - Rani Sofya; Menik Kurnia Siwi; Oknaryana Oknaryana (Universitas Negeri Padang, 2018)
The Competitiveness of Indonesian Humans according to Business World In 2018 it was ranked 45th out of 63 countries,and meaning that Indonesian lower than neighboring countries such as Malaysia. To improve competitiveness, education is needed for the people of Indonesia. Various policies have been implemented to increase education participation. In fact there are still students who drop out of school at all levels of education in Indonesia. The research was conducted to identify the characteristics of the socio-economic conditions of families dropping out of school in the city of Padang. The study was conducted by distributing questionnaires to 36 students who dropped out of school. Based on the data obtained it is known that students who drop out dominantly come from families with low and middle income economies. Parents of dominant students have primary and secondary education. The work of parents who drop out of school is mostly farmers, fishermen and laborers. Based on these results it is recommended that students and families shoul be have a strong commitment to the importance of education so that they can improve family conditions so that they can emerge from the vicious circle of poverty.